Inositol phosphate kinase 2 is required for imaginal disc development in Drosophila. - Seeds, A.M.; Tsui, M.M.; Sunu, C.; Spana, E.P.; York, J.D. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Inositol phosphate kinase 2 (Ipk2), also known as IP multikinase IPMK, is an evolutionarily conserved protein that initiates production of inositol phosphate intracellular messengers (IPs), which are critical for regulating nuclear and cytoplasmic processes. Here we report that Ipk2 kinase activity is required for the development of the adult fruit fly epidermis. Ipk2 mutants show impaired development of their imaginal discs, the primordial tissues that form the adult epidermis. Although disk tissue seems to specify normally during early embryogenesis, loss of Ipk2 activity results in increased apoptosis and impairment of proliferation during larval and pupal development. The proliferation defect is in part attributed to a reduction in JAK/STAT signaling, possibly by controlling production or secretion of the pathway's activating ligand, Unpaired. Constitutive activation of the JAK/STAT pathway downstream of Unpaired partially rescues the disk growth defects in Ipk2 mutants. Thus, IP production is essential for proliferation of the imaginal discs, in part, by regulating JAK/STAT signaling. Our work demonstrates an essential role for Ipk2 in producing inositide messengers required for imaginal disk tissue maturation and subsequent formation of adult body structures and provides molecular insights to signaling pathways involved in tissue growth and stability during development.